2021
DOI: 10.1111/pops.12781
|View full text |Cite
|
Sign up to set email alerts
|

Facing a Common Human Fate: Relating Global Identity and Climate Change Mitigation

Abstract: Collective efforts of the world community are required to mitigate global climate change. Understanding oneself as part of this world community might be crucial for individual behavior change reducing carbon emissions. We examined whether a global identity (i.e., the identification with all humans and a concern for their well‐being) is related to self‐reported climate‐protective behavior in two studies. In a German quota sample (N = 498), global identity was positively related to the personal and societal rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…Our study’s results align with previous research showing that the more people perceive all humanity as an ingroup that requires care, the more concerned they are about the environment and the more involved in pro-environmental behavior ( Loy et al, 2021 ). It is also in line with the SIMPEA ( Social Identity Model of Pro-Environmental Action ), linking the process of social identification with the relevance of climate change and climate-protective behavior ( Loy et al, 2021 ; Masson and Fritsche, 2021 ). Categorizing oneself as a member of all humanity promotes people’s engagement in prosocial behaviors, including pro-ecological behaviors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study’s results align with previous research showing that the more people perceive all humanity as an ingroup that requires care, the more concerned they are about the environment and the more involved in pro-environmental behavior ( Loy et al, 2021 ). It is also in line with the SIMPEA ( Social Identity Model of Pro-Environmental Action ), linking the process of social identification with the relevance of climate change and climate-protective behavior ( Loy et al, 2021 ; Masson and Fritsche, 2021 ). Categorizing oneself as a member of all humanity promotes people’s engagement in prosocial behaviors, including pro-ecological behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Studies on IWAH confirmed its crucial positive role in predicting concern for humanitarian behavior ( Hamer et al, 2019 ). IWAH was also positively related to pro-environmental attitudes ( Lee et al, 2015 ), pro-environmental behavior ( Loy and Reese, 2019 ), and the relevance attributed to the global crisis of climate change ( Loy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have thus examined the relevance of a global identity (i.e., perceiving a group membership with all humanity, McFarland et al, 2012 , 2019 ), for counteracting environmental crises (e.g., Running, 2013 ; Der-Karabetian et al, 2014 ; Barth et al, 2015 ; Joanes, 2019 ; Loy and Reese, 2019 ; Loy and Spence, 2020 ; Loy et al, 2022a ). Loy et al (2022b) , for example, argued that global identity could serve as driver to act in collective instead of self-interests when it comes to climate change mitigation. They found that identification with people all over the world predicted self-reported climate-protective behavior and behavioral intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, where people believe climate impacts take place might be influenced by their mental models (Bostrom, 2017) of climate change, but also by their sources of climate information (e.g., media, social circle) and their willingness to take in new information (e.g., through Bayesian updating; Cook & Lewandowsky, 2016). How they feel towards those locations might be impacted by the physical distance between the locations and themselves (often used as PD), but also their familiarity with them (Yang et al, 2020), whether they care about them (Objects of Care, Wang, Leviston, Hurlstone, Lawrence, & Walker, 2018), whether they feel similar to and identify with the people in the impacted places (global identity, e.g., Loy, Reese, & Spence, 2021;Social Identity Approach, e.g., Mackay, Schmitt, Lutz, & Mendel, 2021), as well as personal characteristics such as empathy (e. g., Chu & Yang, 2019) or cognitive styles (e.g., holistic and analytical thinking, e.g., Sacchi et al, 2016).…”
Section: Bottom-up Research In Action: Understanding Different Types ...mentioning
confidence: 99%